The Mediating Role of Internalizing Problems on the Relationship between Emotional Well-being and Externalizing Problems of Divorced Women in Zanjan - loghman ebrahimi; Yalda Rostami; Maryam Mohamadlou (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Due to the increasing number of divorces and their irreparable consequences, divorced women are at increasing risk of these problems. Objectives: The present study aimed to analyze the mediating role of internalizing problems on the relationship between emotional well-being and externalizing problems of divorced women in Zanjan. Methods: The method in this research was descriptive correlation carried out through survey method. The statistical population was all divorced women in Zanjan that 200 people were selected through convenience sampling. Questionnaires of anxiety-depression-stress scale (DASS-21), emotional well-being (Keys and Magyar-Mae, 2003), and AGQ aggression as well as and Fisher divorce adjustment scale (1976) were applied to collect data. Structural equation modeling test and EMUs software were used to analyze the data. Results: The research findings indicated that there is a significant relationship, which is in reverse and decreasing, between emotional well-being and externalizing problems (aggression) and internalizing problems. There is a significant relationship, which is direct and increasing, between emotional well-being and externalizing problems (post-divorce adjustment) and internalizing problems (depression, anxiety and stress) with externalizing (aggression) problems of divorced women. There is also a significant relationship between internalizing problems and externalizing problems (post-divorce adjustment) in reverse and decreasing, and the variable of internalizing problems is a mediating variable in the relationship between emotional well-being and externalizing problems. Conclusion: Based on the findings of the present study, with increase in emotional well-being, internalizing and externalizing (aggression) problems decrease and post-divorce adjustment increases in women. Accordingly, responsible institutions are required to take the needed measures in the form of training workshops and psychological services to recover and improve emotional well-being among these people.